SISTEM PENENTUAN RUTE PENDISTRIBUSIAN PRODUK AIR MINERAL MENGGUNAKAN ALGORITMA ANT COLONY SYSTEM - Nugraha, Deny Wiria; Erwin Dodu, Albrecht Yordanus; Septiana, Stevi (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2019)
The problem of determining distribution routes can be categorized as Traveling Salesman Problem (TSP). TSP is a search for a sequence of locations where a salesman travels from the initial location to a list of locations which must be passed. Each location can only be visited once and ends at the initial location of departure. This study aims to resolve the problem of determining the distribution route for mineral water products at PT. Anugerah Wina Sentosa by implementing the Ant Colony System (ACS) algorithm to conduct route searches. The ACS algorithm is an algorithm adopted from the behavior of ants to determine the shortest route from the nest to the food source. Based on the research, the results of the ACS algorithm show that the greater the case to be resolved will affect the system execution time but still can produce the best distance route. The success of this algorithm is influenced by the determination of the value of the ACS parameter, namely β, qo, q, α, ?, the number of ants and the number of ant cycles determined by analyzing the TSP case to be resolved.